2019
DOI: 10.12957/reuerj.2019.30338
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de uma intervenção educacional de enfermagem em pacientes portadores de DPOC

Abstract: Objetivo: avaliar os efeitos imediatos da orientação do plano de alta hospitalar aos pacientes com DPOC. Método: estudo prospectivo, comparativo, realizado num hospital privado de São Paulo, com pacientes com DPOC. Na primeira etapa foi aplicado questionário “Plano educacional para pacientes com DPOC” para avaliar conhecimento do paciente sobre sua doença. Na segunda etapa foi realizada intervenção educacional e na terceira, reaplicação do questionário. A comparação do resultado do pré e pós-teste foram feitas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…The Dorothea Orem's Self-Care Deficit Theory (6) is part of a model of professional practice that focuses on the meaning of self-care and the various factors that affect its provision. The specificity of this theory is identified in relation to therapy follow-up, since, for adherence, it is necessary a continuous educational process between nurses and individuals who, comprising the orientations received, appropriate their treatment and commit to its performance (7) . Therefore, it is suggested that using this theory may help professionals exposed to potentially contaminated biological material to adhere to prophylactic treatment of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The Dorothea Orem's Self-Care Deficit Theory (6) is part of a model of professional practice that focuses on the meaning of self-care and the various factors that affect its provision. The specificity of this theory is identified in relation to therapy follow-up, since, for adherence, it is necessary a continuous educational process between nurses and individuals who, comprising the orientations received, appropriate their treatment and commit to its performance (7) . Therefore, it is suggested that using this theory may help professionals exposed to potentially contaminated biological material to adhere to prophylactic treatment of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al [25] lembram que é essencial que a prática de exercícios físicos faça parte destas ações educativas para pacientes com DPOC, pois o aumento dos níveis de atividade é crucial para gestão da doença, podendo resultar em melhora do prognóstico a longo prazo. Em contrapartida, a inatividade física está associada à exacerbação do quadro.…”
Section: Discussionunclassified